DEVELOPING ISLAMIC ECONOMICS AS A BODY OF KNOWLEDGE: ISSUES AND CHALLENGES - HAFAS FURQONI (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2016)
Abstract. Developing Islamic Economics as a Body of Knowledge: Issues and Challenges. Islamic economics is challenged whether it can be called a discipline in the sense of having a clear subject-matter, well-organized body of knowledge, methodology to appraise theories and systematic accumulation of knowledge. Islamic economics is still in the formative stage to be a discipline. Systematization of its body of knowledge is still in the progress. Many fundamental issues need to be seriously addressed by the scientific community for Islamic economics to be a legitimate discipline. This paper attempts to identify several challenges to be answered by Islamic economics scientific community in their effoert to develop a solid body of knowledge of Islamic economics. Embarking from the Islamic worldview that gives foundations in our understanding of economic phenomena, efforts are to be put to develop the conceptual scheme, methodology to appraise and evaluate theory and Islamic ethics framework. The answer to those challenges will determine the scientific direction of Islamic economics, ensurea sustainable growth of knowledge and expedite the speed of the evolutional process of Islamic economics towards becoming a distinct discipline.Abstrak. Mengembangkan Ekonomi Islam sebagai Inti dari Ilmu Pengetahuan: Masalah dan Tantangan. Ekonomi Islam ditantang apakah itu dapat disebut disiplin dalam arti materi yang jelas, inti dari ilmu pengetahuan yang terorganisir dengan baik, metode untuk menilai teori dan akumulasi sistematis ilmu pengetahuan. Ekonomi Islam masih dalam tahap formatif untuk menjadi suatu disiplin. Sistematisasi bod nya pengetahuan masih dalam kemajuan. Banyak masalah mendasar perlu ditangani serius oleh komunitas ilmiah untuk ekonomi Islam menjadi disiplin yang sah. Tulisan ini mencoba untuk mengidentifikasi beberapa tantangan yang harus dijawab oleh ekonomi Islam komunitas ilmiah dalam effoert mereka untuk mengembangkan tubuh yang kuat dari pengetahuan ekonomi Islam. Memulai dari pandangan dunia Islam yang memberikan dasar-dasar dalam pemahaman kita tentang fenomena ekonomi, upaya yang harus dihukum untuk mengembangkan skema konseptual, metodologi untuk menilai dan mengevaluasi kerangka teori dan etika Islam. Jawaban untuk tantangan-tantangan akan menentukan arah ilmiah ekonomi Islam, ensurea pertumbuhan yang berkelanjutan pengetahuan dan mempercepat kecepatan proses evolusional ekonomi Islam menuju menjadi disiplin yang berbeda.